Tourism economics and policy analysis: Contributions and legacy of the Sustainable Tourism Cooperative Research Centre. (March 2016) - Dwyer, Larry; Forsyth, Peter; Spurr, Raymond
Abstract: The Centre for Economic Policy (CEP) located within Australia's Sustainable Tourism Cooperative Research Centre, engaged with government, industry and researchers for over a decade to advance policy analysis in tourism contexts. This paper discusses the contributions of the CEP in three major areas-the development of tourism satellite accounts, economic impact analysis and policy evaluation. The conceptual and empirical work undertaken by CEP, and the fertile research agenda it developed, is incomplete and poses an ongoing challenge to tourism researchers, practitioners and destination managers internationally to help to progress the advances already made.